Fertirrigação nitrogenada em cultivares de maxixeiro cultivadas em substrato de fibra de coco - de Oliveira, Francisco de Assis; de Oliveira, Mychelle Karla Teixeira; Lima, Luan Alves; Bezerra, Francisco Mardones Servulo; Alves, Rita de Cássia [UNESP]; Linhares, Paulo Sérgio Fernandes (My University, 2015)
Fruts of gherkin are highly appreciated in the Brazilian cuisine, however, they have still been little studied. The study was developed to evaluate the effect of nitrogen fertigation on gherkin cultivars grown in substrate of coconut fiber. A completely randomized and factorial design (3 x 4) was used with four replicates, being three cultivars of gherkin (Liso de Calcutá, Liso Gibão and Maxixe do Norte) and four nitrogen concentrations (50, 100, 150 and 200 mg L-1). A total of five fruit harvests were carried out and the following variables were evaluated: longitudinal and cross-sectional diameters, number of fruits, mean fruit weight and total yield per plant. Statistical analysis showed that the Liso de Calcutá cultivar stood out, as it presents greater number of fruits (25.7) and higher yield (640.7 g plant-1). The cultivars had different responses to increasing concentrations of Nitrogen in the nutrient solution. For cultivation of gherkin in coconut fiber, the nutrient solution with Nitrogen concentration of 134 and 129 mg L-1 is recommended for the Liso de Calcutá and Maxixe do Norte cultivars, respectively, and 50 mgL-1 of N for the Liso Gibão cultivar.
Nitrogen fertigation in gherkin cultivars grown in substrate of coconut fiber
Keywords: Cucumis anguria L. hydroponics; Nitrogen; Nutrient solution